Dipyrone, scopolamine, and meloxicam for conventional or two-port laparoscopic-assisted ovariohysterectomy in female dogs - Dalmolin, Fabíola; Oliveira, Marília Teresa; Pinto Filho, Saulo Tadeu Lemos; Vaz, Marcos André Braz; Cecco, Bianca Santana de; Feranti, João Pedro Scussel; Carvalho, Elizabeth Regina; Silva, Marco Augusto Machado; Brun, Maurício Veloso (Semina: Ciências Agrárias, 2020)
For ethical and organic reasons, surgical and analgesic techniques that minimize and adequately control pain should be studied. Ovariohysterectomy is the most common surgical technique in veterinary medicine and is performed in female dogs for elective or therapeutic purposes. Both conventional and minimally invasive surgical techniques are used in veterinary medicine; however, the minimally invasive laparoscopic technique is considered superior to the conventional technique because it is associated with a less painful and faster post-operative recovery. However, for various reasons, the laparoscopic technique is not yet widely used in veterinary medicine, and the conventional ovariohysterectomy is still the most common. The aim of this study, therefore, was to validate the efficacy of the combination of dipyrone, scopolamine, and meloxicam after conventional or two-port laparoscopic-assisted ovariohysterectomies in female dogs. Additionally, this study sought to assess recovery after the two surgical modalities while receiving the same analgesic protocol. Fourteen healthy adult female dogs were spayed and then evaluated using the Visual Analogue Scale, the Melbourne Scale, and the short form of the Glasgow Composite Measure Pain Scale for 72 hours after surgery. The analgesic protocol was efficient for pain control after both techniques, with minimal differences between the groups.